Comparison of measured and calculated magnetic fields along the Ulysses orbit. Issue 3 (1st February 2015) - Svirzhevsky, N.S.; Bazilevskaya, G.A.; Svirzhevskaya, A.K.; Stozhkov, Yu.I.
Abstract The existence of close relations between the temperature, density and velocity of the solar plasma and the heliospheric magnetic field (HMF) was shown along the space probe Ulysses orbit. A simple mathematical formula describing a relation between the HMF and the solar plasma temperature and density was introduced and the expected values of the HMF were calculated using daily and hourly Ulysses data. Correlation coefficients and regression equation between the values of the measured and calculated magnetic fields have been defined. An origin of the peaks in the magnetic field which are observed in the heliospheric sector zone near the corotating interaction regions is discussed as well as the specific role of plasma density and temperature in the formation of magnetic peaks.